Post-Industrial and Digital Society - Croeser, Sky (Palgrave Macmillan, 2018)
This handbook unites leading scholars from around the world in exploring anarchism as a political ideology, from an examination of its core principles, an analysis of its history, and an assessment of its contribution to the struggles that ...